2022
DOI: 10.1038/s41598-022-19199-0
|View full text |Cite
|
Sign up to set email alerts
|

SICA-mediated cytoadhesion of Plasmodium knowlesi-infected red blood cells to human umbilical vein endothelial cells

Abstract: Zoonotic malaria due to Plasmodium knowlesi infection in Southeast Asia is sometimes life-threatening. Post-mortem examination of human knowlesi malaria cases showed sequestration of P. knowlesi-infected red blood cells (iRBCs) in blood vessels, which has been proposed to be linked to disease severity. This sequestration is likely mediated by the cytoadhesion of parasite-iRBCs to vascular endothelial cells; however, the responsible parasite ligands remain undetermined. This study selected P. knowlesi lines wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although all blood-stage forms of Pk circulate, recent data suggest that a subset of Pk-iRBCs demonstrate endothelial cytoadherence (sequestration), which is a key mechanism for the microvascular accumulation of Pf -iRBCs [74][75][76][77][78]. A recent study of Pk malaria in rhesus macaques, a non-natural host, was conducted by the Emory National Primate Research Center [74].…”
Section: Cytoadhesion and Sica Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all blood-stage forms of Pk circulate, recent data suggest that a subset of Pk-iRBCs demonstrate endothelial cytoadherence (sequestration), which is a key mechanism for the microvascular accumulation of Pf -iRBCs [74][75][76][77][78]. A recent study of Pk malaria in rhesus macaques, a non-natural host, was conducted by the Emory National Primate Research Center [74].…”
Section: Cytoadhesion and Sica Antigensmentioning
confidence: 99%
“…Pk sequestration is likely dependent on Schizont-Infected Cell Agglutination (SICA) antigens. These protein antigens, encoded by the SICAvar gene family, are only expressed on iRBCs when a functional spleen is present [74,77].…”
Section: Cytoadhesion and Sica Antigensmentioning
confidence: 99%
“…A high proportion of severe Pk infections has been reported in Southeast Asia (5,19), as well as fatal cases (18)(19)(20). A recent study also showed that, similarly to P. falciparum, Pk-infected erythrocytes are able bind to endothelial cells (21). Postmortem findings in one fatal case of severe Pk malaria revealed brain pathology features similar to those seen in fatal falciparum cerebral malaria, including Pk-infected erythrocytes sequestration in the microvasculature (18), suggesting that Pk malaria may also affect the brain.…”
Section: Introductionmentioning
confidence: 99%